PERSIAN ECHOES IN THE ARCHIPELAGO: Exploring Shi‘a Aesthetics and Ritual Memory in Indonesian Islam - Maulana, Maulana; Hanafi, Imam (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This article examines the presence of Persian Shi‘a ritual aesthetics in Indonesian Islam through a case study of two Muharram commemorations: the Tabuik festival in Pariaman, West Sumatra, and the Tabok ritual in Palembang, South Sumatra. Though practiced within predominantly Sunni communities, these rituals retain symbolic, theatrical, and affective elements historically associated with Shi‘a mourning traditions in the Persianate world. Drawing on theories of cultural memory (Assmann, Connerton), ritual aesthetics (Chelkowski, Aghaie, Hyder), and Persianate cosmopolitanism (Pollock, Green, Ahmed), the article argues that such practices are not aberrations but culturally adapted expressions of a broader Islamic memory. By tracing the localized afterlives of Karbala in Indonesia, this study reveals the plural genealogies of Islamic devotion in the archipelago. It contributes to a deeper understanding of Islam’s transregional aesthetic and emotional vocabularies.